Organizational flexibility of airlines during COVID-19: A study on the airline companies in Turkey - Sercan Demir; Ersin Aktas; Turan Paksoy (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: COVID-19 caused a highly uncertain environment and introduced a radical change in the airline industry. In that time, idle capacity due to drastic decline in passenger traffic, change in travel rules, and increases in air cargo demand have emerged as the main challenges. Effective responses to these issues became a fundamental requirement for airlines' survival and sustainability of supply chains. Organizational flexibility plays a vital role in dealing with those situations. Flexibility allows airline companies to adapt to changing environmental conditions and take advantage of opportunities. This study aims to explain the strategies of airline companies in Turkey to the COVID-19 crisis based on organizational flexibility. Methodology: This study is structured on the qualitative research method. We interviewed five experts and compiled information by reviewing various publications on COVID-19. We analyzed obtained information within the framework of organizational flexibility. Findings: The results indicated that airlines mitigate the effects of COVID-19, mostly through protective and exploitative maneuvers of organizational flexibility. Airlines focus more on cost reduction and saving strategies as protective maneuvers, while exploitative maneuvers focus more on the cargo market. Originality: This study is novel in that it examined airlines' responses to COVID-19 within the framework of organizational flexibility.
urn:nbn:de:gbv:830-882.0161775; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security